Intrauterine contraception after cesarean section and during lactation: a systematic review - Goldstuck ND; Steyn PS (Dove Medical Press, 2013)
Norman D Goldstuck,1 Petrus S Steyn2 1Department of Obstetrics and Gynaecology, Tygerberg Hospital, Cape Town, Western Cape, South Africa; 2Reproductive Health and Fertility Regulation, Department of Obstetrics and Gynaecology, Groote Schuur Hospital and University of Cape Town, Cape Town, South Africa Background: All postpartum women, including those who are breastfeeding or have had a cesarean section, appear potentially suited to intrauterine contraception, a long acting reversible contraceptive (LARC). Like any other method used after delivery, it should not interfere with lactation or be affected by cesarean section. Study design: We searched the MEDLINE, PubMed, Popline, Google Scholar, and Clinicaltrials.gov databases from January 1968 through to December 2012. Studies were included if they reported event rates in women who had a cesarean section and event rates and clinical outcomes in lactating women or their infants in the breastfeeding group. Summary odds ratios were not calculated because of the diverse methods of reporting event rates in the cesarean section group and the heterogeneity of the results in the breastfeeding group. Results: We found 26 articles on event rates in interval and post-placental intrauterine device (IUD) use, and 18 on event rates and clinical outcomes in breastfeeding IUD users. Four prospective studies and one retrospective study showed an increased expulsion rate in interval insertion. There were 19 studies, of which five were controlled in post-placental IUD insertion after cesarean section. Four studies had expulsion rates of 10 or more per 100 woman-years of use and 15 expulsion rates below 10 per 100 woman-years of use. Three studies showed that event rates for lactating IUD users are the same as those for non-lactating users. Fifteen controlled studies showed that the IUD had no effect on milk production and seven of these showed no effect on infant growth. Pharmacovigilance databases report an increased rate of IUD perforations in lactating women, while the event rate studies report that insertion is generally easier and less painful than expected. These were uncontrolled reports. Conclusion: The IUD is a long-acting reversible method of contraception with expulsion rates of 5–15 per 100 woman-years of use when used as a post-placental method immediately after cesarean section. As an interval procedure (6 or more weeks after cesarean section) it appears to have a high expulsion rate (5% or higher) notably in older devices. The IUD does not affect breastfeeding and is easy to insert in these women, but appears to be associated with a higher perforation rate (>1 per 100). Providers should not be deterred from using this contraception method, especially in developing countries, but should be attentive to preventing these potential problems. Keywords: long acting reversible contraception, IUD, cesarean section, post-placental, lactation